SIGNIFICANCE OF THE STEPWISE SURGICAL APPROACH TO SEVERE HAND INJURY - Trutyak, I.R.; Kalynovych, N.R.; Trutyak, R.I.; Hnateiko, N.O. (World of Medicine and Biology, 2020)
Сontinuous one step surgical procedures on the hand in polytraumatised patients and patients with hand multi structural injured increase risk of complications and are life-threatening. The aim of our work was to evaluate the effectiveness of the stepwise surgical approach to severe hand injury. Stepwise surgical approach according “damage control” concept was applied for 28 (1.5 %) severe hand injured civilian polytraumatised patients, for 621 (32 %) multi structural hand injured patients, for 12 (34 %) multiple military wounded patients and for 23 (66 %) military multi structural hand wounded patients. The good and satisfactory hand function we received in 78.5 % polytraumatised patients and in 94.9 % patients with multi structural hand injuries, in 4.3 % – despite the hand salvage, its function was unsatisfactory. Amputations was performed at the level of the forearm in 7 patients, 5 patients died from shock and life-threatening injuries.